Analysis of air traffic controllers' mental workload and visual search efficiency to assess new air traffic control procedures - Ko, Kelvin Chi Kin (2019)
With a global rise in air travels, advancements in Air Traffic Management is necessary to meet the demands. One such improvement is the concept of dual orientation visualisation of air traffic information, addressing the disadvantages in 2D orientation. However, given the slow industry uptake for this concept, this study aims to examine the disadvantages of this concept to address the reluctance. Subjects were recruited to partake in an experiment involving various permutations of 2D and 3D orientations to investigate potential loss in spatial memory, visual search efficiency and gains in mental workload induced with dual orientation usage. Performance, eye tracking, and subjective scale data sources were collected and used to investigate the hypothesis. Analysis indicates that having a dual orientation system does increase spatial memory loss, lower visual search efficiency and an increase in mental workload. While this lends weight to the argument against having a dual orientation system, it was also shown that 3D orientation augments relative positioning tasks that negate spatial memory losses. While this study highlights some of the concerns regarding dual orientation systems, it raises an area of focus for future research, where dual orientation systems could be leveraged on with the segmentation of tasks